Стан інтродукційних популяцій видів роду Galanthus L. (Amaryllidaceae) флори Кавказу в умовах Києва. Частина 1. Ендемічні види - Didenko, S.Ya. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The results of 62 years of the introduction of the genus Galanthus L. species of flora of the Caucasus in botanical-geographical area Caucasus of M.M. Gryshko National Botanical Gardens of the NAS of Ukraine. The results of two years of research of natural populations snowdrops in the Caucasus are given.